FULL DIALLEL ANALYSIS OF PEA CULTIVARS FOR SEED WEIGHT AND ITS COMPONENTS UNDER KURDISTAN REGION-IRAQ CONDITION - Ahmed, Omed Haji; Tofiq, Sherwan I.; Abdulkhaleq, Dana A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The present study was carried out at Grjan Agricultural Research Station and Qaladze Agricultural Research Station, College of Agricultural Engineering Sciences-University of Raparin, Kurdistan Region-Iraq, during the growing seasons 2020 and 2021. According to the full diallel mating system using five pea (Pisum sativum L.) cultivars (Legacy, Rainer, Topaz, P11, P13) with 20 F1 crosses. The genotypes were planted in a RCBD with 3 replicates. Highly significant mean squares due to genotypes for all traits were recorded in both locations. The mean squares due to the GCA were highly significant for all of the traits except for number of days to 50% flowering which was significant at Grjan, but at Qaladze it was highly significant for number of days to maturity, pod length, seeds weight pod-1, and 100-seed weight. The mean squares due to SCA were highly significant for all of the traits except for 100-seed weight which was significant and was not significant for number of seeds pod-1 and seeds weight pod-1 at Grjan, but at Qaladze it was highly significant for all of the traits except for significant pod length, and it was not significant for seeds weight pod-1. The highest positive heterosis value for seeds weight plant-1 at Grjan was 177.445% recorded by the diallel cross 3×4, while at Qaladze it was 210.431% recorded by the diallel cross 1×3. The reciprocal cross 5×3 had the maximum heterosis value for seeds weight plant-1 at 78.300%, while at Qaladze it was 199.713% recorded by the reciprocal cross 5×2. The maximum positive GCA effect values for most of the traits were recorded by the parent P13 at both locations. The dominance gene effect controlled the inheritance of most of the traits of both locations.